Synthesis of novel dimeric subphthalocyanines via azide-alkyne Huisgen 1,3-dipolar cycloaddition and palladium-catalyzed Glaser-Hay coupling reactions - Goktug, Ozge; Gol, Cem; Durmuş, Mahmut (World Sci Publ Co Inc, 2017)
In this study, the monomeric subphthalocyanines bearing azido (2) and terminal ethynyl (3) groups were synthesized. These subphthalocyanines were converted to their dimeric derivatives using azide-alkyne Huisgen cycloaddition and palladium-catalyzed Glaser-Hay coupling reactions subphthalocyanine (4) and (5), respectively. The novel subphthalocyanines were fully characterized by elemental analysis and general spectroscopic methods such as MALDI-TOF mass, FT-IR, UV-vis and H-1-NMR. All synthesized subphthalocyanines showed quite good solubility in the most of common organic solvents. The fluorescence measurements were conducted for these subphthalocyanines to estimate their fluorescence quantum yields. The singlet oxygen generation abilities were also examined to investigate their photosensitizer properties.
Keywords: subphthalocyanin; boron; singlet oxygen; fluorescence; photosensitizer